EFFECTIVE PSYCHEDUCATION TO REDUCE ANXIETY AND INCREASE COMPLIANCE OF LIQUID DIETS IN CHRONIC KIDNEY DISEASE PATIENTS DURING HEMODIALYSIS - Meylani Dewi Wowor; Ni Luh Widani; Emiliana Tjitra (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: Chronic kidney failure (chronic renal failure) is a chronic disease that causes disruption of kidney function, so it requires kidney replacement therapy with long-term hemodialysis that must comply with fluid diets and can cause anxiety. Aims: Research to assess the effect of nursing psychoeducation on reducing anxiety levels and adherence to fluid diets in chronic renal failure patients with hemodialysis. Methods: The study was conducted in April-July 2018 in three private hospitals in Tomohon and Manado. This research is a quantitative study with a quasi-experimental pre-post test design with a control group of 112 respondents (82 in the intervention group and 30 in the control). Psychoeducation interventions are given according to the education module for 4 weeks, 2 times a week for a total of 8 meetings. Anxiety was assessed using the Beck Anxiety Inventory (BAI) questionnaire and adherence was assessed by the End Stage Renal Disease-Adherence Questionnaire (ESRD-AQ) before and after the study and weight observations at each visit. Results: Wilcoxon test results showed significant differences in anxiety levels (p <0.005) and fluid diet compliance (p <0.005) before and after the intervention. Mann Whitney test results showed no significant difference in decreasing anxiety level (p = 0.456) and increasing levels of fluid diet compliance (p = 0.495) between the intervention and control groups. The results of the ordinal logistic regression test, psychoeducation reduced anxiety levels by an OR of 6.5 times compared to the control group. The results of the binary logistic regression test, psychoeducation increased the level of adherence to the liquid diet with an OR value of 2.4 times compared to the control group. Conclusion: Psychoeducation can help reduce the level of anxiety and adherence to the fluid diet of patients with chronic renal failure with hemodialysis.